2022
DOI: 10.1029/2022gl098926
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Tropical Cyclone Pressure Tendency on Size

Abstract: Current theories of tropical cyclone (TC) intensification give little direct indication of the role of the TC size in intensity changes, although there are observations showing a relationship. We develop a new model of TC central pressure tendency where the pressure change can be expressed as exponential with a time constant determined by the ratio of radius maximum wind (Rmax) and the column inflow or outflow speed. An analysis of observations confirms the relationship which becomes more important for a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Sparks and Toumi (2022a) showed how surface pressure increases are driven by the net inflow into the column for a weakening storm. The pressure tendency depends on both the inflow and the size of the cyclone (Sparks & Toumi, 2022b). Their framework does not invoke inertial stability and is consistent with the observations here.…”
Section: Discussionmentioning
confidence: 99%
“…Sparks and Toumi (2022a) showed how surface pressure increases are driven by the net inflow into the column for a weakening storm. The pressure tendency depends on both the inflow and the size of the cyclone (Sparks & Toumi, 2022b). Their framework does not invoke inertial stability and is consistent with the observations here.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we treated RI as an extreme‐detecting problem and cluster the initial V max and RMW, with a subsequent ΔV 24 for all global TCs from 2004 to 2020. These variables were selected because they define the initial state of the vortex before RI, as demonstrated by previous theoretical and observational studies (e.g., Carrasco et al., 2014; Li et al., 2021; Mallen et al., 2005; Y. Wang et al., 2021; Sparks & Toumi, 2022) and our sensitivity experiments. Over 12,000 events extracted from the IBTrACS best‐track data were clustered using the K‐Means clustering algorithm; one cluster with a minimum ΔV 24 of 45 kt/24hr (23.2 m/s/24hr) was thereby distinctly separated from the others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the vortex size reflects feedback between the primary circulation and inner‐core processes (Mallen et al., 2005; Sparks & Toumi, 2022), and affects the subsequent intensification (Emanuel, 1989). Studies based on best‐track data have confirmed that RI events rarely occur when RMW is larger than 100 km because a small RMW favors intensification due to the conservation of angular momentum (Carrasco et al., 2014; Xu & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A weak dependence of TC size on intensity has been observed 25 , 26 , as has an important increase of size during the decay of a TC which contributes to the footprint of any damage 27 . We represent this behaviour within our model.…”
Section: Methodsmentioning
confidence: 99%